2019
DOI: 10.3389/fimmu.2019.00948
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts on 6-sulfo LacNAc Expressing Monocytes (slanMo)

Abstract: The human mononuclear phagocytes system consists of dendritic cells (DCs), monocytes, and macrophages having different functions in bridging innate and adaptive immunity. Among the heterogeneous population of monocytes the cell surface marker slan (6-sulfo LacNAc) identifies a specific subset of human CD14 − CD16 + non-classical monocytes, called slan + monocytes (slanMo). In this review we discuss the identity and functions of slanMo, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 135 publications
(257 reference statements)
1
37
0
Order By: Relevance
“…From animal experiments, we know that chronic UVB exposure can induce skin carcinomas and chronic solar UV exposure is clearly associated with skin carcinomas in humans . It is attractive to hypothesise that an aberrantly heightened skin immunity in psoriasis underlies this discrepancy …”
Section: The Actual Evidence For Optimal Efficacy and Safety Accordinmentioning
confidence: 99%
“…From animal experiments, we know that chronic UVB exposure can induce skin carcinomas and chronic solar UV exposure is clearly associated with skin carcinomas in humans . It is attractive to hypothesise that an aberrantly heightened skin immunity in psoriasis underlies this discrepancy …”
Section: The Actual Evidence For Optimal Efficacy and Safety Accordinmentioning
confidence: 99%
“…However, tumor-infiltrating DCs can also be defective in their functional activity and can contribute to immune suppression (14). For example, we have shown that a higher density of 6-sulfo LacNAc monocytes (slanMo), representing a subset of human non-classical blood monocytes that can differentiate into DCs (15), is significantly associated with a poor prognosis of clear cell renal cell cancer (RCC) patients (16). The tumor-infiltrating slanMo displayed an immature phenotype and expressed IL-10, which may explain this correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Functional analysis of this interaction revealed a significantly decreased phagocytic capacity and antigen-presenting ability of monocytes and macrophages when co-cultured with UC-MSCs. Furthermore, we investigated the impact of MSCs on various immunomodulatory properties of 6-sulfo LacNAc monocytes (slanMo), representing a subset of pro-inflammatory CD14 – CD16 + non-classical monocytes, which may contribute to the pathogenesis of various inflammatory diseases ( Ahmad et al, 2019 ). We found that MSCs profoundly suppress the capacity of slanMo to secrete TNF-α, IL-6, and IL-12, improve their IL-10 production, and efficiently inhibit the slanMo-induced proliferation of CD4 + and CD8 + T cells ( Wehner et al, 2009 ).…”
Section: Modulation Of Innate Immunity By Mscsmentioning
confidence: 99%